PELAYANAN BIDAN PADA MASA ADAPTASI KEBIASAAN BARU DI RSUD. DOLOK SANGGUL - Hutajulu, Johansen; Simanjuntak, Novita K; Ompusunggu, Tanti Yosepha (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
The Corona Virus Disease-2019 (covid-19) pandemic has resulted in many changes to the service order as a hospital entrance. Midwives must adjust services to patients so as to minimize the risk of transmission of COVID-19. The purpose of this study was to explore the experience of midwives in providing hospital services during the adaptation period to new habits at the Dolok Sanggul Hospital. This research is an exploratory qualitative research with a phenomenological approach. The population in this study were all midwives at the Dolok Sanggul Hospital. The technique of taking participants was done by purposive sampling as many as 6 participants. Data collection using interviews. The data were analyzed using the trial version of Nvivo 12 software. The results of this study obtained 7 (seven) , namely 1) Implementing infection prevention and control procedures, 2) Implementing work safety and safety procedures, 3) Implementing 3M procedures, 4) Anticipating the transmission of covid-19, 5) Providing services to Covid-19 patients. 19 and non-covid-19, 6) Limiting access to hospitals, 7) Utilizing information technology for health service innovation. It is recommended that midwives continue to carry out infection control and prevention procedures, occupational safety and health as well as 3M procedures (washing hands, wearing masks, maintaining distance) to anticipate the transmission of COVID-19.